Reaching the Final Endgame for Constant Waves of COVID-19 - Norman Ratcliffe (Viruses, 2022)
Despite intramuscular vaccines saving millions of lives, constant devastating waves of SARS-CoV-2 infections continue. The elimination of COVID-19 is challenging, but necessary in order to avoid millions more people who would suffer from long COVID if we fail. Our paper describes rapidly advancing and innovative therapeutic strategies for the early stage of infection with COVID-19 so that tolerating continuing cycles of infection should be unnecessary in the future. These therapies include new vaccines with broader specificities, nasal therapies and antiviral drugs some targeting COVID-19 at the first stage of infection and preventing the virus entering the body in the first place. Our article describes the advantages and disadvantages of each of these therapeutic options which in various combinations could eventually prevent renewed waves of infection. Finally, important consideration is given to political, social and economic barriers that since 2020 hindered vaccine application and are likely to interfere again with any COVID-19 endgame.